Análise de um modelo matemático de localização na reorganização de uma rede logística estabelecida - D'Andréa, Rafael (2011)
The increasing competition among the supply chains generated by economic globalization and technological innovation has required logistics networks becoming increasingly complex. Thus, planning of logistics networks has become increasingly important and the location of facilities a strategic issue in search of competitive advantage. This study is included in a stream of research about the facilities location theory and aims to analyze a logistics network established by setting the amount and location of one or more distribution centers to minimize the total costs associated with the chain as a whole, without compromising the level of service. To this end, a nonlinear programming model is proposed in order to solve a real problem of a company in the oil sector. It also proposed a method of analysis for facility location problems, which lists the main steps to be followed. Finally, it presents a sensitivity analysis in order to obtain managerial insights, where various scenarios will be generated and optimized. The results obtained by computer simulation using the AIMMS software were adequate to solve the proposed problem, with the conclusions reached in agreement with the literature.